Untouchable : the strange life and tragic death of Michael Jackson - Sullivan, Randall (New York : Grove Press, 2012)
Traces the story of Michael Jackson's life from his famous childhood through his final four years, drawing on interviews with his friends, enemies, and other associates to cover his international travels, business acumen, and parenting decisions.
Includes bibliographical references (p. [611]-776).
Keywords: Jackson, Michael, -- 1958-2009.; Jackson, Michael, -- 1958-2009 -- Death and burial; African American rock musicians -- Biography; Rock musicians -- United States -- Biography; African American singers -- Biography; Singers -- United States -- Biography; Rock musicians -- United States -- Death; Rock music -- United States -- Biography